ANTHRAX IN THE TERRITORY OF YAMAL: ASSESSMENT OF EPIZOOTIOLOGICAL AND EPIDEMIOLOGICAL RISKS - E. G. Simonova; S. A. Kartavaya; A. V. Titkov; M. N. Loktionova; S. R. Raichich; V. A. Tolpin; E. А. Lupyan; A. E. Platonov (Проблемы особо опасных инфекций, 2017)
Objective of the study was to analyze epizootiological and epidemiological risks contributing to the development of anthrax outbreak in the Yamal peninsular in July-August, 2016. Materials and methods. Risks were evaluated using complex approach allowing for determination of the impact of epidemiologically significant social, natural, and biological risks, based on literature sources, archival data, and statistical reports. Special focus was on the natural-climatic factors, providing for persistence of the agent in the environment, such as NDVI index, atmospheric temperature and humidity, as well as soil temperature and moisture at different depths, in accordance with satellite monitoring. Results and conclusions. Justified was the hypothesis on sustained adversity of soil foci in Yamal, remaining hazard of aggravation of epizootiological and epidemiological situation on anthrax against the background of changing environmental and social risk factors, as well as agent ability to survive in the soils within an indeterminate amount of time.